Analisis Kinerja Ruas Jalan Raya Babat Akibat Aktivitas Pasar Tradisional Babat - Assyifa, Moh Zahdi; Tjendani, Hanie Teki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Babat-Bojonegoro Road, located directly in front of the Babat Traditional Market in Lamongan, is a 2/2-UD type road with a total width of 11 meters and a lane width of 5.5 meters. This road frequently experiences congestion, especially during peak hours such as in the morning and late afternoon, due to high activity levels around the market area. This study aims to evaluate the performance of this road segment using observational methods based on the Indonesian Highway Capacity Guidelines (PKJI) 2023. The analysis shows that the highest traffic flow reaches 2,842 vehicles per hour, with a traffic volume of 1,614.2 pcu/hour. The side friction is categorized as high, with 700 events per hour. The road capacity is recorded at 2,184 pcu/hour, with a free-flow speed of 32.76 km/h and an average travel speed of 24 km/h. Travel time is around 58 seconds. The degree of saturation is 0.73, and the level of service is rated C, indicating stable flow with limited maneuverability.